2020
DOI: 10.1111/are.14780
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperature affects growth and hemato‐biochemical parameters, inducing morphological abnormalities of erythrocytes in Nile tilapiaOreochromis niloticus

Abstract: Temperature is considered as an important environmental factor, and the increasing water temperature resulting from global warming is a great concern. The present study was conducted to examine the effects of elevated water temperature on growth, hemato‐biochemical parameters in Nile tilapia, Oreochromis niloticus acclimatized to three temperatures (31°C, 34°C and 37°C) for 60 days. Additionally, erythrocytic cellular abnormalities (ECA) and erythrocytic nuclear abnormalities (ENA) tests were assayed using per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…The balanced sex ratio of O. niloticus does not deviate significantly even up to 36 • C [92]. A study on the haemato-biochemical parameters also revealed that temperatures up to 34 • C may not be hazardous for Nile tilapia [96]. A comparative study suggests that embryonic development and hatching of carp are significantly affected even at 33 • C [112].…”
Section: Temperature Fluctuationmentioning
confidence: 94%
See 3 more Smart Citations
“…The balanced sex ratio of O. niloticus does not deviate significantly even up to 36 • C [92]. A study on the haemato-biochemical parameters also revealed that temperatures up to 34 • C may not be hazardous for Nile tilapia [96]. A comparative study suggests that embryonic development and hatching of carp are significantly affected even at 33 • C [112].…”
Section: Temperature Fluctuationmentioning
confidence: 94%
“…Table 2 summarizes the effects of temperature changes on the physiological alterations of tilapia. The thermal effects on tilapia showed that growth performance significantly decreased after at 34 • C, although this showed a decreasing tendency towards high temperature changes [91][92][93][94][95][96]. Before they reached 5 days old tilapia (O. mossambicus) showed significantly increased percentages of deformity, and a greater number of males was induced by high temperature (28 and 32 • C) after 10 days [97].…”
Section: Temperature Fluctuationmentioning
confidence: 99%
See 2 more Smart Citations
“…Islam et al, 2019) while hematocrit %, hemoglobin quantity and total proteins were measured according to earlier protocols(Hussain et al., 2019; Ghaffar et al 2020) at days 15, 30, 45 and 60 of the experiment. Serum biochemical studies For different serological parameters, serum was separated from the blood of each sh placing on ice at different experimental intervals at days 15, 30, 45 and 60 of the experiment.…”
mentioning
confidence: 99%